UPRAWNIENIA PRZYSŁUGUJĄCE PODMIOTOM, WOBEC KTÓRYCH ZASTOSOWANO PODSŁUCH ELEKTRONICZNY W ŚWIETLE PRAWA NIEMIECKIEGO - Musialik-Dudzińska, Gabriela (Wydział Prawa i Administracji UAM, 2001)
According to German legislation there function both procedural and extra-procedural electronic bugging, that is bugging, whose objects are statements made not in public, in a flat or outside it, regardless of the telecommunication traffic. Drawing upon the legal norms in operation, the author discusses some basic rights granted to the parties subject to acoustic invigilation and, above all, the right of obtaining information about the use of electronic bugging. Further on, the author deals with the right, granted to every citizen, to commission the control of accordance with the law and the way the directive of bugging was executed - both in a flat and outside it. The last section of the paper is devoted to the right of pursuing claims for indemnity at instances, where bugging was being used against the law, violating the service duty or by parties not entitled to it.
THE RIGHTS OF PARTIES, WHO HAVE BEEN ELECTRONICALLY BUGGED IN THE LIGHT OF GERMAN LAW